[Illustration of a young girl holding a plate on which there is food; she carries it towards an elderly woman who is seated beside a tree and who reaches out her hands to take it from the girl]. - Fagan, George, 1879-1907.; Holloway, Joseph, 1861-1944 (1902)
Black and white illustration on paper with other pen and ink sketches on verso of sheet. [The artist George Fagan also often signed his name "Ua Fágáin" and 'S. Uí Fhágáin'].
Keywords: Girls -- Clothing & dress -- Ireland -- 1900-1910.; Women -- Clothing & dress -- Ireland -- 1900-1910.; Ink drawings -- Irish -- 1900-1910; Pen works -- Irish -- 1900-1910